Disentangle the factorial structure of Ecotourism Experiential Value (EEV) and Its Effects on Total Eco-tourist Experience Quality (TEEQ) and Eco-tourist Behavioural Intentions (EBI): an analysis of Taman Negara National Park - Musa, Rosidah; Muhammad Kassim, Rezian-na; Putit, Lennora (2012)
The tourism industry around the world are under intense pressure to gain into insights and identify the underlying key factors that drive tourist experience quality. It is critical for tourism operators to unravel the underlying factors that stimulate tourist experience because they will lead to favourable behaviour and attitude such as feel attached to the destination and actively engaging in activities that promote the destination through sharing experience via word of mouth and social network media (download picture and video via u-tube, facebook, twitter etc). The tourism industry should go beyond service excellence and provide experiential value which would lead the creation of memorable experience. In fact research finding reveals that nowadays customers not only expect a quality experience; they demand it. Even though the concept of customer experience has dominated many contemporary discussions among practitioners and academics; however there has been conspicuously little empirical investigation of the concept to disentangle the factors that contribute to 'ecotourism experiential value' (EEV) and in turn identifying its consequences which are crucial in advancing knowledge in this new emerging research area. Thus, this research aims to fill the void by undertaking an empirical investigation to disentangle the underlying factors structure of EEV and examine its effect on Total Eco-tourist Experience Quality (TEEQ) and in turn on eco-tourists destination attachment and interpersonal engagement. Subsequently, this study will verify the plausibility of the hypothesised framework in the context of ecotourism setting. The research model will be tested on a data of 225 visitors of TNNP. The finding unveils that EEV is a six-factorial structure which comprises of: aesthetics, escapism, social bonding, service value, economic value and knowledge enrichment. Three of these factors (aesthetics, escapism and social bonding) have significant effect on TEEQ. The study concludes that TEEQ significantly influenced two approach behaviours which are destination attachment and interpersonal engagement. In view for the measurement scales and research model to be widely accepted and adopted by others, cross country validation is recommended. The study has important implications for future research directions and management of ecotourism destination.